A Step Impedance Microstrip Filter for Microwave RFID Application - Gina Haziza Ariani; Asrizal; Mairizwan (Research on Instrumentation, 2024)
RFID is an automatic identification technology that uses electromagnetic waves to transmit and receive information stored in tags or responders upon request from an RFID reader. To ensure that only signals with the working frequency of the RFID reader enter the reader, the signals are filtered first using a filter. A filter is a transition device designed to pass desired frequencies while eliminating or attenuating undesired frequencies. Therefore, a lowpass microstrip filter is designed for RFID microwave applications to limit the radio wave frequencies used in the RFID system. The designed lowpass microstrip filter has a cut-off frequency of 2.4 GHz, an insertion loss of -3 dB, a return loss of -10 dB, and an input impedance of 50 ohm. The lowpass filter is implemented on a microstrip substrate NPC-H220A. variations in the physical design of the microstrip filter can affect the signal performance in achieving the desired cut-off frequency, insertion loss, and return loss. Thus, lowpass microstrip filters with different dimensions are designed. The result of these dimensional changes will be analyzed to determine which design yields the best performance that meets the desired specifications. This research is based on S-Parameters measured using a Vector Network Analyzer (VNA). According to the S-Parameter, S11 represents the return loss, which indicates how well the filter avoids signal reflection back to the source. The smaller the S11 value, the better the filter performance in reducing reflections. S21 represents the insertion loss, measuring the signal loss as it passes through the filter. The smaller the S21 value, the more efficient the filter, indicating that a larger signal successfully passes through the filter